PENGUJIAN MONDAY EFFECT PADA BURSA EFEK INDONESIA DAN BURSA EFEK SINGAPURA - Haikel Ardinan (STIE Perbanas Surabaya, 2014)
The study attempts to examine the influence of Monday effect on stock return. The Monday effect is an example of a seasonal anomaly that is when the stock return is significantly negative on Monday. The variable used is the return index. The population in this study is the IndonesianStock Exchange and the Singapore Stock Exchange. The samples used were LQ45 and the Straits Times Index (STI) in the period January 2010 - December 2012. Statistical methods were used to test the hypothesis covering ANOVA, multiple regression, linear regression. First, it can be concluded that there is no effect on the phenomenon Monday LQ45 and STI during the period 2010-2012. Second, it can also be concluded that the returns on Monday in LQ45 and STI are not concentrated at week 4 and week 5 during the period 2010-2012. The third results in this study it can be concluded that the LQ45 index returns and STI on Monday systematically unpredictable based on market conditions Friday the previous week during the period 2010-2012.